Pendampingan deteksi mandiri sindrom metabolik melalui pemeriksaan IMT, obesitas sentral, tekanan darah, dan pemeriksaan kadar kolesterol - Susilawati Susilawati; Puji Rizki Suryani; Rara Inggarsih; Masayu Farah Diba; Septi Purnamasari (Fakultas Kedokteran Universitas Sriwijaya, 2020)
The shift in eating patterns generally in urban communities where the composition of food consumed tends to be higher in fat and low in fiber. Bad sleep quality due to heavy work, is also a risk factor for various health problems such as hypertension, obesity, insulin resistance and dyslipidemia; we call it metabolic syndrome. Many studies have shown that the number of morbidity and mortality due to metabolic syndrome increases significantly. Community service activities in the form of counseling about raising public awareness about metabolic syndrome, especially people in the village of Talang Petai. Aim of this activity is to increase awareness to carry out prevention and health care activities through dietary arrangements, sleep patterns, increasing physical activity, and immediately check into a health service if there are signs and symptoms of disease. The results of this activity, there is an increase in public knowledge about the dangers and how to promote and prevent metabolic syndrome. Henceforth, it needs to be done continuous community service activities so that health status can be increased.